Predictive factors of fatal bleeding in acute promyelocytic leukemia. Issue 164 (April 2018) - Mantha, Simon; Tallman, Martin S.; Devlin, Sean M.; Soff, Gerald A.
Abstract: Acute promyelocytic leukemia (APL) is associated with a profound coagulopathy. Based on retrospective assessments, several potential risk factors for hemorrhagic morbidity and mortality have emerged. Several studies have shown elevated white blood cell (WBC) count at presentation to be a robust predictor of bleeding events. Other clinical and laboratory parameters have been evaluated with variable association with hemorrhagic morbidity or mortality. These include ECOG performance status, age, morphological subtype, platelet count, peripheral blood blast count, ethnicity, body mass index, prothrombin time, activated partial thromboplastin time, lactate dehydrogenase, d -dimers, creatinine and fibrinogen levels. Unfortunately, most of those assessments were based on a small patient sample and the results have been at times contradictory in terms of which parameters are independent predictors. More recently, two large retrospective studies have reported on the issue. They included data from several international trials of chemotherapy for APL, one on adults and the other focused on the pediatric population. Importantly, both analyses found that WBC count at presentation is the main predictor of early hemorrhagic death and early thrombo-hemorrhagic death, respectively. Much remains to be done if the rate of induction mortality in APL is going to be reduced significantly. One approach would be to incorporate the known risk factors for early hemorrhagic death into a risk stratification system and devise personalized transfusion interventions to meet an individual patient's risk, which could be evaluated in future randomized trials. Highlights: Acute promyelocytic leukemia (APL) is associated with primary hyperfibrinolysis. White blood cell count is a predictor of hemorrhagic early death (HED) in APL. Much work remains to further delineate useful predictors of HED in APL.